2017
DOI: 10.1016/j.ijrobp.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Job Shortage or Job Maldistribution? A Geographic Analysis of the Current Radiation Oncology Job Market

Abstract: Purpose To examine whether permanent radiation oncologist (RO) employment opportunities vary based on geography. Methods and Materials A database of full-time RO jobs was created by use of American Society for Radiation Oncology (ASTRO) Career Center website posts between March 28, 2016, and March 31, 2017. Jobs were first classified by region based on US Census Bureau data. Jobs were further categorized as academic or nonacademic depending on the employer. The prevalence of job openings per 10 million popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
(22 reference statements)
3
15
0
Order By: Relevance
“…The analysis reported here within supports this conclusion as only 50% of residents trained in the Northeast were employed there, which is significantly lower than the rate of trainees in the South (66%) and West (70%) who stayed in their respective regions for employment. Chowdhary et al also demonstrated that the Midwest had more jobs available than the number of graduating residents, with roughly two trainees for every three jobs (proportion of total jobs to graduates, 1.54) [13]. This study's findings suggest that Midwest-trained graduates are just as likely to take these jobs as graduates from other regions.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The analysis reported here within supports this conclusion as only 50% of residents trained in the Northeast were employed there, which is significantly lower than the rate of trainees in the South (66%) and West (70%) who stayed in their respective regions for employment. Chowdhary et al also demonstrated that the Midwest had more jobs available than the number of graduating residents, with roughly two trainees for every three jobs (proportion of total jobs to graduates, 1.54) [13]. This study's findings suggest that Midwest-trained graduates are just as likely to take these jobs as graduates from other regions.…”
Section: Discussionsupporting
confidence: 48%
“…A point of contention is whether residents' dissatisfaction with the current job landscape is due to an oversupply of ROs, a maldistribution of ROs, or a combination of both. Chowdhary et al [13] shed light on this topic. The authors demonstrated that the Northeast trains far more residents than jobs available in that region with roughly five trainees for every four jobs (proportion of total jobs to graduates, 0.78).…”
Section: Discussionmentioning
confidence: 99%
“…3 Interestingly, a majority of jobs were either located in the Midwest (n Z 51, 23.7%) or South (n Z 60, 27.4%), reflecting a potential mismatch in positions sought (ie, West Coast) versus those that are currently offered. 3 Figure 3 gives the geographic distribution of all posted positions by job type in 2018, including an additional 38 part-time jobs, locums, or instructor positions, for a total of 257 unique postings. Accurate information regarding the distribution of available jobs is important to graduating residents and medical students considering RO.…”
mentioning
confidence: 99%
“…Significant regional imbalances of academic versus nonacademic radiation oncology jobs, regional job availability, and a surplus of radiation oncology trainees may exist in the Northeast. 20 There are also more National Cancer Institute–designated cancer centers in the Northeast and South Atlantic regions than other regions in the United States. One study found that the further patients live from a radiation center, the less likely they are to choose radiation for their prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are likely similar to those previously described for RT, namely the increased proportion of academic centers in the Northeast. 20 …”
Section: Discussionmentioning
confidence: 99%